Determination of arms and legs contribution to propulsion and percentage of coordination in breaststroke swim - Shahbazi-Moghaddam, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
In the present study, the Indirect Measurement of Active Drag (IMAD) was used to study the contribution of the legs and arms to propulsion in breaststroke swim. Contrary to the Measuring of Active Drag (MAD) system, the IMAD can be used for all strokes and therefore enabled us to study the breaststroke swim to estimate not only the percentage of legs and arms contribution to propulsion but also the percentage of swimmers` arms and legs co- ordinations. The method revealed that the best coordination was 87.8% and that the contributions of arms and legs in propulsive force were 67% and 65% and in velocities were 97.7% and 98.2%, respectively, showing that the swimmers received equal contributions from the arms and legs in propulsion and velocity during breaststroke swim.